Evidence for multiple early impacts on the H chondrite parent body from electron backscatter diffraction analysis - Goudy, Secana P.; Telus, Myriam; Chapman, Brendan (Meteoritics & planetary science, 2023)
We examined H4 chondrites Beaver Creek, Forest Vale, Quenggouk, Ste. Marguerite, and Sena with the electron backscatter diffraction (EBSD) techniques of Ruzicka and Hugo (2018) to determine if there is evidence for shock metamorphism consistent with the previously inferred histories of their early impact excavation or lack thereof. We find that all samples have EBSD data consistent with a history of synmetamorphic impact shock (i.e., shock during thermal metamorphism), followed by postshock annealing. Petrographic analysis of Sena, Quenggouk, and Ste. Marguerite found exsolved Cu and irregular troilite within Fe metal, features consistent with shock metamorphism. All samples have a spatial variability in grain deformation consistent with shock processes, though Forest Vale, Quenggouk, and Ste. Marguerite may have relict signatures of accretional deformation as indicated by variability in their olivine deformation metrics. Within the context of previous workers' geochemical observations, a more complex history is inferred for each sample. The “slow‐cooled” samples, Quenggouk and Sena, were subject to synmetamorphic shock without excavation and annealed at depth. The same is true of the “fast‐cooled” samples, Beaver Creek, Forest Vale, and Ste. Marguerite. However, after annealing, these rocks were excavated by a secondary impact or impacts around 5.2–6.5 Ma post‐CAI formation and were left to cool rapidly on the surface of the H chondrite parent body. These interpreted histories are best compatible with a model of an impact‐battered but intact onion shell for the earliest history of the H parent body. However, the EBSD evidence does not preclude a parent body disruption after 7 Ma post‐CAI formation.